2014
DOI: 10.3928/01477447-20140528-64
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Retrograde Osteochondral Autologous Transplantation to Chondral Lesion in Femoral Head

Abstract: This report describes the treatment of 2 cases of full-thickness cartilage defect of the femoral head. The authors performed osteochondral autologous transplantation with a different technique that has not been reported to date. One patient was 37 years old, and the other was 42 years old. Both presented with hip pain. In both patients, radiograph and magnetic resonance imaging scan showed a focal chondral defect on the weight-bearing area of the femoral head and acetabular impingement. A retrograde osteochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…A technique for arthroscopic assisted autologous OT for the femoral head has also been reported [ 31 ]. In this procedure, a tunnel is created from the lateral cortex of the femur via the femoral neck and into the chondral defect.…”
Section: Resultsmentioning
confidence: 99%
“…A technique for arthroscopic assisted autologous OT for the femoral head has also been reported [ 31 ]. In this procedure, a tunnel is created from the lateral cortex of the femur via the femoral neck and into the chondral defect.…”
Section: Resultsmentioning
confidence: 99%
“…The arthroscopic technique used in the present report is a new concept being first described by Çetinkaya et al [13]. They used a retrograde osteochondral autograft transplantation technique combined with hip arthroscopy in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that cartilage defects are moderately common in dysplastic hips 36 and proved to be highly correlated with hip pain, stiffness, and dysfunction in movement and function. 611 Repair of cartilage defects in the hip has been reported to yield good clinical and radiologic outcomes through osteochondral 7 or chondrocyte 35 transplantation. To date, however, a systematic evaluation of the improvement in functionality, physical health, quality of life, and tolerability in association with the cartilage repair after transplantation of periosteal autografts has not yet been performed in dysplastic hip in older children.…”
Section: Discussionmentioning
confidence: 99%